DEVELOPMENT OF DISC THROWING EXERCISE MODEL FOR BEGINNERS - Ucok Hasian Refiater; Arief Ibnu Haryanto (UNG, 2022)
This research aims to develop a discus throwing exercise model for beginners. This study has a population of 10 beginner discus throwers at the Gorontalo State University. The novelty in this research is research related to the development of the disc flash exercise model for beginners. The method used in this research is development research adopted by the ADDIE model development research design. The place for conducting this research is the field of Campus 3, State University of Gorontalo. Data were collected by observation, interviews, and questionnaires. The stages of data collection are carried out in the early stages, which consist of five stages starting Analysis, Design, Development, Implementation, and Evaluating. The results of the study prove that from the results of the evaluation of athletic experts, it was obtained that this product as a whole met the eligibility criteria so that it could be used in the next stage of research. The conclusion is seen and proven that the development of this discus throwing exercise model is effective in increasing the throwing results.Keywords: developme; disc throwing; exercise model.